2018
DOI: 10.29252/nfsr.5.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Chemical, Nutritional and Antioxidant Characteristics of Roselle (Hibiscus sabdariffa L.) Seed

Abstract: A B S T R A C TBackground and Objectives: Roselle (Hibiscus sabdariffa L.) is one of the valuable plants grown in tropical and subtropical regions such as some parts of Iran. Roselle calyces are commonly used to make herbal tea as well as a natural food color additive. However, Roselle seeds are usually discarded as by-products, while they can be used as a source of nutritious and functional compound. Therefore, in the current study, some of the chemical and nutritional characteristics of Iranian Roselle seed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 21 publications
1
8
1
Order By: Relevance
“…The family consists of 243 genera and Hibiscus is among the largest genera in terms of number of species [7,15]. The species of this genus (Hibiscus) are well known for their showy flowers and thus known as Hibiscus or Rose mallow [16,17]. A large number of epidemiological studies showed that the use of antioxidant vitamins and carotenoids inhibits the development of cancer [18][19]9], coronary heart disease [20], atherosclerosis [21] and hepatoprotective [22].…”
Section: Review Of Literaturementioning
confidence: 99%
“…The family consists of 243 genera and Hibiscus is among the largest genera in terms of number of species [7,15]. The species of this genus (Hibiscus) are well known for their showy flowers and thus known as Hibiscus or Rose mallow [16,17]. A large number of epidemiological studies showed that the use of antioxidant vitamins and carotenoids inhibits the development of cancer [18][19]9], coronary heart disease [20], atherosclerosis [21] and hepatoprotective [22].…”
Section: Review Of Literaturementioning
confidence: 99%
“…The main fatty acids identified are linoleic (39.31%), oleic (32.06%), palmitic (20.84%) and stearic (5.88%). Besides seeds, leaves and calyxes are widely used in cooking and traditional medicine in countries such as Mexico, India, England, China and Brazil (Nasrabadi, Zarringhalami, & Ganjloo, 2018;Singh, Khan, & Hailemariam, 2017;Nzikou et al, 2011l).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the crude protein content of kenaf seed as ranging from 21.4% to 30.5% (Alexopoulou et al, 2013;Kim et al, 2018;Mariod et al, 2010;Nyam et al, 2009;Olawepo et al, 2014), similar to the protein composition of hemp seed, that is, 23.8% to 28.0% (Vonapartis et al, 2015). These values are higher than the protein content of Roselle seed (14.9%) (Nyam et al, 2009) but are lower than the values of 33.5% and 26.62% reported by Hainida, Amin, Normah, and Esa (2008) and Mokhtari, Zarringhalami, and Ganjloo (2018), respectively for crude protein of Roselle seed. The defatted kenaf seed has higher protein content (ranging from 74.4% to 81.4%) than the whole seed (Mariod et al, 2010).…”
Section: Proteins Composition Of Kenaf Seedmentioning
confidence: 96%